Capabilities, strategies and firm performance in the United Kingdom. Issue 1 (7th February 2019) - Parnell, John; Brady, Malcolm
Abstract : Purpose: The purpose of this paper is to investigate the influence of internal capabilities and environmental turbulence on market (e.g. cost leadership and differentiation) and nonmarket (e.g. political and social) strategies (NMS), and considers how these strategies impact financial and non-financial performance in firms in the United Kingdom. Design/methodology/approach: A survey was administered online to 215 practicing managers in the UK. Measures for competitive strategy (i.e. cost leadership and differentiation), NMS, strategic capabilities, market turbulence and firm performance were adopted from or based on previous work. Hypotheses were tested via SmartPLS. Findings: Findings underscore the impact of market turbulence across all market and nonmarket strategy dimensions. Multiple links between capabilities and strategies were identified. Both cost leadership and differentiation were significantly linked to non-financial performance, but only differentiation was significantly linked to financial performance. An increased emphasis on social NMS was linked to higher financial performance, but not non-financial performance. Political NMS was linked to neither financial nor non-financial performance. Research limitations/implications: The sample included managers in multiple industries. Self-typing scales were utilized to measure market turbulence, emphasis on capabilities, strategic emphasis and firm performance. Practical implications: Emphasis on social NMS can promote financial performance, but political NMS does not appear to drive either financial or non-financial performance. Originality/value: This paper provides empirical support for a UK-based model linking market turbulence, strategic capabilities, market and nonmarket strategies, and both social and firm performance. It supports NMS as a key performance driver, but with caveats.